OPTIMALISASI PRODUKTIFITAS PROSES PERAKITAN SAXOPHONE DI PT.YAMAHA MUSICAL PRODUCTS INDONESIA MENGGUNAKAN METODE HEIJUNKA - Yusron rijal; Moch.Buyung Ilham (SPIRIT, 2016)
The complexity of the problem as production and customer desires will be good quality, cost efficient, and precise and rapid delivery today, demanding the industrialized world make improvements.PT.YMPI is a manufacturing enterprise field saxophone musical instrument, make improvements to meet consumer demand, and refers to the toyota production system. Repairs carried out the planned production plan according Heijunka method which is the basis for the implementation of the Toyota System. Problems that occur on the saxophone is consumer demand that is always changing and there is no proper control tools. Analysis results suggested a very regular production not only made if there is customer demand can be met quickly.Keywords: Heijunka Methode, PT.YMPI, Saxophone Assembly